2020
DOI: 10.4236/ojneph.2020.103021
|View full text |Cite
|
Sign up to set email alerts
|

Managing a Hemodialysis Unit in Times of Pandemic to COVID-19. Experience of Edith Lucie Bongo Ondimba General Hospital

Abstract: This is the description of the prevention and the development of the sessions of hemodialysis in our center hemodialysis to not be contaminated coronavirus. Actions taking are: respect of the measures decreed by the state for prevention. Although these measures are difficult socio-cultural for Africans, they became normal after two weeks. The hemodialysis is made free during this period in our public center. Indeed, the session of hemodialysis was 10,000 francs Africans financial community (CFA in french) or 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Most studies reported that PRHD had anorexia and nausea, like this study. 43,44 A study reported that the odds of reduced appetite, nausea, and vomiting were significantly higher in patients with ESRD than in predialysis patients with CKD. 45 However, GIS showed a significant association with poor appetite and lower serum urea and creatinine unrelated to hemoglobin and albumin.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies reported that PRHD had anorexia and nausea, like this study. 43,44 A study reported that the odds of reduced appetite, nausea, and vomiting were significantly higher in patients with ESRD than in predialysis patients with CKD. 45 However, GIS showed a significant association with poor appetite and lower serum urea and creatinine unrelated to hemoglobin and albumin.…”
Section: Discussionmentioning
confidence: 99%
“…The modest increase in the cost of haemodialysis has great implications since almost all the patients pay out of pocket for heamodialysis. Ngbabe et al reported that in Congo, heamodialysis is made free to all patients during the pandemic [6]. The initiative is highly commendable.…”
Section: Scarcity and Increase In The Cost Of Consumables For Heamodimentioning
confidence: 99%
“…COVID-19 pandemic has the potential to increase poverty and health inequalities especially in low income countries. It is advocated that the federal government should assist patients by making haemodialysis procedure free as reported in some other African countries like Congo[6] during this pandemic to reduce the health and socioeconomic burdens of the pandemic on patients with kidney failure. Inclusion of heamodialysis care of patients in the COVID-19 palliative measures offered by the federal government will be of huge benefit to the patients.…”
mentioning
confidence: 99%